2019
DOI: 10.1371/journal.pone.0201939
|View full text |Cite
|
Sign up to set email alerts
|

Opposing effects of impulsivity and mindset on sources of science self-efficacy and STEM interest in adolescents

Abstract: Impulsivity has been linked to academic performance in the context of Attention Deficit Hyperactivity Disorder, though its influence on a wider spectrum of students remains largely unexplored, particularly in the context of STEM learning (i.e. science, technology, engineering, and math). STEM learning was hypothesized to be more challenging for impulsive students, since it requires the practice and repetition of tasks as well as concerted attention to task performance. Impulsivity was assessed in a cross-secti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Students in the intervention and comparison groups completed surveys before (within one week) and after (within two weeks) the Introduction and Immersion programs. Evaluation instruments and timelines are described in Appendix C and include measures of STEM interest ( Byars-Winston et al, 2010 ; Lent et al, 2003 ), grit ( Duckworth and Quinn, 2009 ), impulsivity ( Steinberg et al, 2013 ), science self-efficacy ( Marriott et al, 2019 ; Usher and Parajes, 2009 ), mindset ( Paunesku et al, 2015 ), motivation and self-determination theory (adapted scale from Deci et al, 2001 for science), biomedical research attitudes ( Cameron, 2005 ), and research self-efficacy ( Weston and Laursen, 2015 ), with the latter reported in this manuscript. Research self-efficacy was measured post-program using the Undergraduate Research Student Self-Assessment (URSSA; Weston and Laursen, 2015 ) which presents five questions on a five-point Likert scale (0=No Gains; 4=Great Gain; Appendix C ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Students in the intervention and comparison groups completed surveys before (within one week) and after (within two weeks) the Introduction and Immersion programs. Evaluation instruments and timelines are described in Appendix C and include measures of STEM interest ( Byars-Winston et al, 2010 ; Lent et al, 2003 ), grit ( Duckworth and Quinn, 2009 ), impulsivity ( Steinberg et al, 2013 ), science self-efficacy ( Marriott et al, 2019 ; Usher and Parajes, 2009 ), mindset ( Paunesku et al, 2015 ), motivation and self-determination theory (adapted scale from Deci et al, 2001 for science), biomedical research attitudes ( Cameron, 2005 ), and research self-efficacy ( Weston and Laursen, 2015 ), with the latter reported in this manuscript. Research self-efficacy was measured post-program using the Undergraduate Research Student Self-Assessment (URSSA; Weston and Laursen, 2015 ) which presents five questions on a five-point Likert scale (0=No Gains; 4=Great Gain; Appendix C ).…”
Section: Methodsmentioning
confidence: 99%
“…Peer mentors supplemented other program mentorship (i.e., community liaisons, scientist partners, community partners, and program staff). Lent et al, 2003), grit (Duckworth and Quinn, 2009), impulsivity (Steinberg et al, 2013), science self-efficacy (Marriott et al, 2019;Usher and Parajes, 2009), mindset (Paunesku et al, 2015), motivation and self-determination theory (adapted scale from Deci et Scientist Evaluation. Feedback from research learning communities, including the laboratory principal investigators and research staff involved with hosting Immersion scholars, was solicited at the end of each of the four two-day placements.…”
Section: Post-program Group Reflection the Ohsu Evaluationmentioning
confidence: 99%
“…Although considered a BAS facet, impulsivity appears to be distinct from the other BAS scales and has been found to be associated with extraversion and low conscientiousness (Dawe & Loxton, 2004;Corr et al, 2013) -which is associated with less favourable attitudes to learning statistics. Additionally, research indicates that impulsivity is associated with lower science self-efficacy (Marriott et al, 2019) and higher trait anxiety in students (Yeo & Lee, 2017). Thus, those high on impulsivity may have a less favourable attitude and given their tendency to act in an unplanned manner, may be less likely to engage in effective learning strategies, such as setting goals, setting aside study time, organizing their learning environment, leading them to experience higher statistics anxiety and lower self-efficacy.…”
Section: Basmentioning
confidence: 99%
“…Learning objectives are meant to provide students and teachers with an end goal for each to know expectations [55], [216], [217]. Some sources suggest placing learning objectives at the beginning of a course or as pre-class content [138], [218].…”
Section: Listing Class Objectivesmentioning
confidence: 99%